Meningkatkan Aktivitas Belajar Peserta Didik pada Mata Pelajaran PAI dan Budi Pekerti Melalui Pembelajaran Kooperatif Model Mind Mapping dalam Bentuk Peta Konsep Kreatif di SMP Negeri 1 Pemenang - Nuning Mulyani (Universitas Pendidikan Mandalika, 2020)
The purpose of this study is to improve student learning activities through cooperative learning Mind Mapping models in the form of creative concept maps. This research method uses classroom action research. The subjects of this study were students of class VII.2 students of SMPN 1 Pemenang with a total of 17 people. This research instrument uses observation. Research data analysis techniques using qualitative and quantitative descriptive analysis. The results of this study indicate that an increase in student learning activities is an average of 12.06 obtained from the average activity of students in the first cycle was 69.06 and then increased in the second cycle to 81.17. So it can be concluded that (1) The application of Mind Mapping learning models in the form of creative concept maps is one of the best alternatives in PAI and Budi Pekerti learning, (2) The application of Mind Mapping learning models in the form of creative concept maps can create participatory and multi-directional learning , (3) Through the application of Mind Mapping learning methods in the form of creative concept maps can increase the learning activities of students. The results also showed changes in classroom atmosphere that tended to be democratic and changes in teacher attitudes to care more about the atmosphere of learning in the classroom.